FINDING DIFFICULTIES IN WRITING EFL - Safitri, Nisfu; Alisha, Fika (IKIP Siliwangi, 2019)
Teaching writing in foreign language has been an interesting topic for researchers. There are many theories and perspective about teaching writing. The main objective of this research is focused on finding out student’s difficulties in writing English. This study used case study with qualitative design. About 30 students are purposively selected as the respondents of the research. The data in this gained through single data collection method was questionnaire. This questionnaire contains 15 closed items and one open ended item. The result indicates students had a significant problem in writing English. The findings revealed that the most significant problems are because of their lack of vocabulary mastery and language used. They assumed that they had limited knowledge in constructing sentence grammatically and also their lack of vocabulary mastery made them felt confused in choosing the word. Besides, they also had problem in spelling. They often left hesitant in writing English word and assumed their spelling is not good enough.